Expression of Interferon Regulatory Factor 4 in Chronic Myeloid Leukemia: Correlation With Response to Interferon Alfa Therapy - Schmidt, Manuel; Hochhaus, Andreas; König-Merediz, Sven A.; Brendel, Cornelia; Proba, Jutta; Hoppe, Georg J.; Wittig, Burghardt; Ehninger, Gerhard; Hehlmann, Rüdiger; Neubauer, Andreas (Journal of clinical oncology, 2000)
PURPOSE: Mice experiments have established an important role for interferon regulatory factor (IRF) family members in hematopoiesis. We wanted to study the expression of interferon regulatory factor 4 (IRF4) in various hematologic disorders, especially chronic myeloid leukemia (CML), and its association with response to interferon alfa (IFN-α) treatment in CML. - - MATERIALS AND METHODS: Blood samples from various hematopoietic cell lines, different leukemia patients (70 CML, 29 acute myeloid leukemia [AML], 10 chronic myelomonocytic leukemia [CMMoL], 10 acute lymphoblastic leukemia, and 10 chronic lymphoid leukemia patients), and 33 healthy volunteers were monitored for IRF4 expression by reverse transcriptase polymerase chain reaction. Then, with a focus on CML, the IRF4 level was determined in sorted cell subpopulations from CML patients and healthy volunteers and in in vitro-stimulated CML cells. Furthermore, IRF4 expression was compared in the CML samples taken before IFN-α therapy and in 47 additional CML samples taken during IFN-α therapy. IRF4 expression was then correlated with cytogenetic response to IFN-α. - - RESULTS: IRF4 expression was significantly impaired in CML, AML, and CMMoL samples. The downregulation of IRF4 in CML samples was predominantly found in T cells. In CML patients during IFN-α therapy, a significant increase in IRF4 levels was detected, and this was also observed in sorted T cells from CML patients. The increase seen during IFN-α therapy was not due to different blood counts. In regard to the cytogenetic response with IFN-α, a good response was associated with high IRF4 expression. - - CONCLUSION: IRF4 expression is downregulated in T cells of CML patients, and its increase is associated with a good response to IFN-α therapy. These data suggest IRF4 expression as a useful marker to monitor, if not predict, response to IFN-α in CML.
Gesehen am 13.04.2022